Modality-specific noun–verb dissociations in L1 but no effect in L2: evidence from bilingual aphasia - Kambanaros, Maria (My University, 2013)
The spoken and written productions of object and action names in two languages of a multilingual speaker with aphasia were compared. The results showed preserved written naming for action words in L1 (Greek) in light of severe difficulties with spoken action names, whereas for object names the opposite pattern was observed. For L2 (English), severe difficulties retrieving action and object names for spoken and written naming were found. The finding supports the widely accepted view that the cognitive processes used for spoken and written naming are relatively independent components that can be selectively impaired after brain injury. In the case of bilingual speakers, the cognitive processes can involve both languages.
Keywords: Bilingual; Aphasia